The effects of nerve terminal activity on non-quantal release of acetylcholine at the mouse neuromuscular junction. - Zemková, H (1990)
1. Local endplate depolarization induced by anticholinesterase application to mouse nerve-diaphragm preparations was taken as a measure of non-quantal release of acetylcholine. 2. Non-quantal acetylcholine release occurred within 20-60 s after anticholinesterase application, either spontaneously or evoked by nerve stimulation. Non-quantal release declined with time and disappeared after 3-5 min. 3. The amplitude of stimulation-evoked non-quantal release increased with the frequency of stimulation and was maximal at frequencies above 50 Hz. Two stimuli were sufficient to evoke the maximal effect. 4. Micromolar concentrations of atropine, pirenzepine and vesamicol reduced the amplitude and shortened the duration of non-quantal release. Oxotremorine (10(-8) M) enhanced the amplitude and ouabain (10(-4) M) prolonged the duration of non-quantal release. 5. Our results support the idea that the non-quantal release is due to the vesicular acetylcholine transport system which becomes transiently a part of the nerve terminal during exocytotic release of quantal acetylcholine.